Unveiling the melodic traditions of Mahzani: an ethnomusicological investigation of Tombulu music in Indonesia's Minahasa region - Pogalin, Deny V. R.; Lestari, Dewi Tika (Institut Seni Indonesia Surakarta, 2023)
This research explores the Mahzani ethnic music tradition, which holds significance among the Tombulu sub-ethnic group of the Minahasa region. As an expression of their cultural identity, Mahzani encapsulates the richness of Tombulu music, encompassing artistic diversity, spiritual values, and the philosophy of life cherished by the Tombulu people. The aim of this study is to analyze the distinctive musical elements that contribute to the unique atmosphere of the Mahzani tradition. This study uses an ethnomusicological approach. This approach collects and analyzes data, namely the melodies of traditional Mahzani music in the cultural context of the Tombulu people as the owners of the music. The ethnomusicological analysis is carried out by analyzing the physical and non-physical forms of Mahzani music to reveal its melodic richness and its aesthetic and philosophical meanings. This comprehensive approach ensures a thorough examination of the musical elements and their cultural implications within the context of the Mahzani tradition. In the end, the result of this research is that the combination of poetry and melody in a single unit of Mahzani's expression at the time has unveiled a unique and mystical atmosphere. At this level, the Tombulu people believe that music has vibrations that are connected to nature and the creator. Music is no longer just a medium for expressing itself, but it is the intention of the expression of human life in relation to their living environment.